Comprehensive Coach Education Reduces Head Impact Exposure in American Youth Football. Issue 10 (15th October 2015) - Kerr, Zachary Y.; Yeargin, Susan W.; Valovich McLeod, Tamara C.; Mensch, James; Hayden, Ross; Dompier, Thomas P.
Background: Despite little evidence that defines a threshold of head impact exposure or that participation in youth sports leads to long-term cognitive impairments, it is prudent to identify methods of reducing the frequency of head impacts. Purpose: To compare the mean number of head impacts between youth football players in practice and games between leagues that implemented the Heads Up Football (HUF) educational program and those that did not (NHUF). Study Design: Cohort study; Level of evidence, 2. Methods: During the 2014 season, head impact exposure was measured using xPatch accelerometers from 70 youth football players aged 8 to 15 years from 5 leagues. Data were collected during both games and practices. The NHUF group comprised 32 players from 8 teams within 3 leagues. The HUF group comprised 38 players from 7 teams within 2 leagues. Independent-sample t tests evaluated differences in head impact exposure across groups (ie, HUF and NHUF). Results: Players (mean ± SD: age, 11.7 ± 1.4 years; height, 152.2 ± 10.5 cm; weight, 51.6 ± 9.6 kg) experienced a total of 7478 impacts over 10 g, of which 4250 (56.8%) and 3228 (43.2%) occurred in practices and games, respectively. The majority of impacts occurred within the NHUF group (62.0%), followed by the HUF group (38.0%). With a 10 g impact threshold, the mean number of impacts during practice per individual event was lower in the HUF group (mean ± SD, 5.6 ± 2.9) than in the NHUF group (mean ± SD, 8.9 ± 3.1; difference, 3.4; 95% CI, 2.9-3.9). This difference was attenuated when the threshold was changed to 20 g but remained significant (difference, 1.0; 95% CI, 0.7-1.3). At both the 10 g and 20 g impact thresholds, no differences were found in games. Conclusion: Players who participated in HUF leagues accumulated fewer head impacts per practice at both the 10 g and 20 g thresholds. Youth football leagues should consider the HUF educational program, while exploring additional interventions, to help reduce the number of head impacts in players.